Overview of Quality of Life in Cancer Patients undergoing Chemotherapy at the Etam Cancer Shelter and Samarinda City Cancer Shelter House - Orin Dwiyanti; Khumaidi; Syahrun; Erwan Ahmad (Fakultas Kedokteran, Universitas Mulawarman, 2025)
Background: A non-communicable disease whose incidence continues to increase every year is cancer. Cancer is the second leading cause of death worldwide. Chemotherapy is a medical treatment that cancer patients must undergo. Chemotherapy causes many effects for cancer patients. This condition can affect the quality of life of cancer patients who do chemotherapy. The purpose of this study is to provide an overview of the quality of life in cancer patients undergoing chemotherapy. Method: The research design used was a quantitative descriptive method with a survey approach. Taking 30 respondents with a consecutive sampling technique based on the inclusion criteria of cancer patients who are undergoing chemotherapy. The quality of life measurement instrument used the WHOQOL-BREF questionnaire with univariate data analysis. Results: The results showed as many as 16 respondents (53%) with poor quality of life, and 14 respondents (47%) had good quality of life. Conclusions: Cancer patients undergoing chemotherapy at the Etam Cancer Shelter and Samarinda City Cancer Shelter have a poor quality of life.